copied all work to Lambda.thy; had to derive a special version of fcb1 for concrete atom
theory Tutorial3s
imports Lambda
begin
section {* Formalising Barendregt's Proof of the Substitution Lemma *}
text {*
The substitution lemma is another theorem where the variable
convention plays a crucial role.
Barendregt's proof of this lemma needs in the variable case a
case distinction. One way to do this in Isar is to use blocks.
A block consist of some assumptions and reasoning steps
enclosed in curly braces, like
{ \<dots>
have "statement"
have "last_statement_in_the_block"
}
Such a block may contain local assumptions like
{ assume "A"
assume "B"
\<dots>
have "C" by \<dots>
}
Where "C" is the last have-statement in this block. The behaviour
of such a block to the 'outside' is the implication
A \<Longrightarrow> B \<Longrightarrow> C
Now if we want to prove a property "smth" using the case-distinctions
P1, P2 and P3 then we can use the following reasoning:
{ assume "P1"
\<dots>
have "smth"
}
moreover
{ assume "P2"
\<dots>
have "smth"
}
moreover
{ assume "P3"
\<dots>
have "smth"
}
ultimately have "smth" by blast
The blocks establish the implications
P1 \<Longrightarrow> smth
P2 \<Longrightarrow> smth
P3 \<Longrightarrow> smth
If we know that P1, P2 and P3 cover all the cases, that is P1 \<or> P2 \<or> P3
holds, then we have 'ultimately' established the property "smth"
*}
subsection {* Two preliminary facts *}
lemma forget:
shows "atom x \<sharp> t \<Longrightarrow> t[x ::= s] = t"
by (nominal_induct t avoiding: x s rule: lam.strong_induct)
(auto simp add: lam.fresh fresh_at_base)
lemma fresh_fact:
assumes a: "atom z \<sharp> s"
and b: "z = y \<or> atom z \<sharp> t"
shows "atom z \<sharp> t[y ::= s]"
using a b
by (nominal_induct t avoiding: z y s rule: lam.strong_induct)
(auto simp add: lam.fresh fresh_at_base)
section {* EXERCISE 10 *}
text {*
Fill in the cases 1.2 and 1.3 and the equational reasoning
in the lambda-case.
*}
lemma
assumes a: "x \<noteq> y"
and b: "atom x \<sharp> L"
shows "M[x ::= N][y ::= L] = M[y ::= L][x ::= N[y ::= L]]"
using a b
proof (nominal_induct M avoiding: x y N L rule: lam.strong_induct)
case (Var z)
have a1: "x \<noteq> y" by fact
have a2: "atom x \<sharp> L" by fact
show "Var z[x::=N][y::=L] = Var z[y::=L][x::=N[y::=L]]" (is "?LHS = ?RHS")
proof -
{ -- {* Case 1.1 *}
assume c1: "z = x"
have "(1)": "?LHS = N[y::=L]" using c1 by simp
have "(2)": "?RHS = N[y::=L]" using c1 a1 by simp
have "?LHS = ?RHS" using "(1)" "(2)" by simp
}
moreover
{ -- {* Case 1.2 *}
assume c2: "z = y" "z \<noteq> x"
have "(1)": "?LHS = L" using c2 by simp
have "(2)": "?RHS = L[x::=N[y::=L]]" using c2 by simp
have "(3)": "L[x::=N[y::=L]] = L" using a2 forget by simp
have "?LHS = ?RHS" using "(1)" "(2)" "(3)" by simp
}
moreover
{ -- {* Case 1.3 *}
assume c3: "z \<noteq> x" "z \<noteq> y"
have "(1)": "?LHS = Var z" using c3 by simp
have "(2)": "?RHS = Var z" using c3 by simp
have "?LHS = ?RHS" using "(1)" "(2)" by simp
}
ultimately show "?LHS = ?RHS" by blast
qed
next
case (Lam z M1) -- {* case 2: lambdas *}
have ih: "\<lbrakk>x \<noteq> y; atom x \<sharp> L\<rbrakk> \<Longrightarrow> M1[x ::= N][y ::= L] = M1[y ::= L][x ::= N[y ::= L]]" by fact
have a1: "x \<noteq> y" by fact
have a2: "atom x \<sharp> L" by fact
have fs: "atom z \<sharp> x" "atom z \<sharp> y" "atom z \<sharp> N" "atom z \<sharp> L" by fact+ -- {* !! *}
then have b: "atom z \<sharp> N[y::=L]" by (simp add: fresh_fact)
show "(Lam [z].M1)[x ::= N][y ::= L] = (Lam [z].M1)[y ::= L][x ::= N[y ::= L]]" (is "?LHS=?RHS")
proof -
have "?LHS = Lam [z].(M1[x ::= N][y ::= L])" using fs by simp
also have "\<dots> = Lam [z].(M1[y ::= L][x ::= N[y ::= L]])" using ih a1 a2 by simp
also have "\<dots> = (Lam [z].(M1[y ::= L]))[x ::= N[y ::= L]]" using b fs by simp
also have "\<dots> = ?RHS" using fs by simp
finally show "?LHS = ?RHS" by simp
qed
next
case (App M1 M2) -- {* case 3: applications *}
then show "(App M1 M2)[x::=N][y::=L] = (App M1 M2)[y::=L][x::=N[y::=L]]" by simp
qed
text {*
Again the strong induction principle enables Isabelle to find
the proof of the substitution lemma completely automatically.
*}
lemma substitution_lemma_version:
assumes asm: "x \<noteq> y" "atom x \<sharp> L"
shows "M[x::=N][y::=L] = M[y::=L][x::=N[y::=L]]"
using asm
by (nominal_induct M avoiding: x y N L rule: lam.strong_induct)
(auto simp add: fresh_fact forget)
subsection {* MINI EXERCISE *}
text {*
Compare and contrast Barendregt's reasoning and the
formalised proofs.
*}
end